Training and empowerment of health activists on physical activities for optimizing cognitive function in the elderly - Anugrahanti, Wisoedhanie Widi; Ariyanti, Rea (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
The covid 19 pandemics that hit Indonesia also impacted aspects of public health, especially for the elderly. The implementation of physical distancing to prevent the transmission of Covid 19 will impact discomfort for all individuals, including the elderly. The elderly are forced to be in their respective homes, which causes the reduced physical activity to reduce endurance. This service aims to improve the understanding and skills of health cadres about physical activity for the elderly and the benefits obtained, including body fitness, increased endurance, and optimization of cognitive function in the elderly. The method used is to provide counseling and skills training for cadres in demonstrating the appropriate forms and types of physical activity for the elderly. The target of this service is Health Cadres in Kalimeri Hamlet, Tambakasri Village, T Kerajinan Subdistrict, Malang Regency. The result of the implementation of this community service activity is that there has been an increase in the knowledge or understanding and skills of health cadres about physical activity for the elderly, where the cadres have become more aware of the importance of carrying out physical activity, especially for the elderly and types of physical activity that are suitable for the elderly.